(3GdJhLjI GdeNJGQ aj faj GdZdH Yf MOjK ENJUGe GdLfI hGdfGQs - (3EHQGgje Hf MSf Hf TgGH GdOjf GdTgQGfj GdTgQRhQqj GdchQGfj, HQgGf GdOjf,J (B1101 (3g` s ((3GdeOjfI GdefhQI s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO fHi GdQMeI hHYO bGd GdfHi Udi Gddg Ydjg hSde (B" (3GdLfg hGdfGQ abGdJ GdfGQ Ch KQJ HGdeJcHQjf hGdeJLHQjf hbGdJ GdLfI eGdi dG jONdfi EdG VYaGA GdfGS s
(3BNQgG (B:s
(3heYdhe Cf GdEdbGA HYO GdEfTGA ajg ERGdg ddTchi hEf hbY GdENQGL ef MjK dG JTYQ hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B35 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B21s
Keywords: (3GdeLGejYs